Legal literacy : an introduction to legal studies - Zariski, Archie M., 1949- (Open paths to enriched learning., 2014)
To understand how the legal system works, students must consider the law interms of its structures, process, language, and modes of thought and argument--in short, they must become literate in the field. Legal Literacy fulfills this aim by providing a foundational understanding of key concepts such as legal personhood, jurisdiction, and precedent, and by introducing students to legal research and writing skills. Examples of cases, stuatues, and other legal materials support these concepts.